Chiral near-fields around chiral dolmen nanostructure. (3rd November 2017) - Fu, Tong; Wang, Tiankun; Chen, Yuyan; Wang, Yongkai; Qu, Yu; Zhang, Zhongyue
Abstract: Discriminating the handedness of the chiral molecule is of great importance in the field of pharmacology and biomedicine. Enhancing the chiral near-field is one way to increase the chiral signal of chiral molecules. In this paper, the chiral dolmen nanostructure (CDN) is proposed to enhance the chiral near-field. Numerical results show that the CDN can increase the optical chirality of the near-field by almost two orders of magnitude compared to that of a circularly polarized incident wave. In addition, the optical chirality of the near-field of the bonding mode is enhanced more than that of the antibonding mode. These results provide an effective method for tailoring the chiral near-field for biophotonics sensors.